USING SIX SIGMA TO EVALUATE ANALYTICAL PERFORMANCE OF HEMATOLOGY ANALYZER - Robiul Fuadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Many medical decisions in the hospital based on hematology examination results, must be aware of their method performance. Sigma-metric is an excellent way to evaluate analytical performance quality. The performance analysis of laboratory hematology analyzer and Cell Dyne Ruby can use Sigma-metric. This study aimed to evaluate the analytical performance of Abbott Cell Dyne Ruby hematology analyzer, by Six Sigma in Clinical Pathology Laboratory of the Dr. Soetomo Hospital Surabaya, Indonesia. Sigma analysis was calculated by a formula, sigma = (TEa – CV)/ Bias. The CLIA proficiency testing criteria specified Total Error Allowable (TEa). The Coefficient of Variant (CV) and bias data were supplied from analyzer running three levels of control Low (L), Normal (N), and High (H) include following analytes: hemoglobin (Hb), Red Blood Cell count (RBC), Hematocrit (HCT), White Blood Cell count (WBC), and Platelet count (PLT). Sigma-value as follows Hb(L:4.33 N:6.68 H:2.62), RBC(L:3.43 N:3.84 H:3.46), HCT(L:2.52 N:1.73 H:2.27), WBC (L:7.14 N:8.44 H:6.38), and PLT (L:2.46 N:8.75 H:7.84). Average Sigma-value for all parameters was 4.75. Minimum Sigma-value for any business or manufacturing process was three. More than Six Sigma-value was a world-class performance. Hematology analyzer Cell Dyne Ruby provides “Good” performance by Sigma-metric.